1980
DOI: 10.1071/bi9800675
|View full text |Cite
|
Sign up to set email alerts
|

Early Follicular Development and Atretic Changes in the Ovary of the Lamb? Fine Structure and Histochemistry

Abstract: The fine structure of follicles was studied in ovaries from lambs up to 32 days old. Some animals received pregnant mare serum gonadotrophin prior to sampling. Follicles examined were in the primordial to early antral stages. The oocyte is described and changes associated with its development and the formation of the zona pellucida are recorded. Characteristics in which the lamb oocyte differed from those of other mammals included a greater prominence of smooth endoplasmic reticulum, the presence of microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…It is important to note that the rupture of the basement membrane was not observed in any of the degenerated follicles studied. Other researches also reported primordial and tertiary follicles at initial and advanced stages of atresia to contain an intact basement membrane (Hay et al, 1976 andTassel andKennedy, 1980). When Types 1 and 2 degenerated follicular data was pooled, it was observed that secondary follicles were more affected by the degeneration than primordial and primary follicles.…”
Section: Discussionmentioning
confidence: 89%
“…It is important to note that the rupture of the basement membrane was not observed in any of the degenerated follicles studied. Other researches also reported primordial and tertiary follicles at initial and advanced stages of atresia to contain an intact basement membrane (Hay et al, 1976 andTassel andKennedy, 1980). When Types 1 and 2 degenerated follicular data was pooled, it was observed that secondary follicles were more affected by the degeneration than primordial and primary follicles.…”
Section: Discussionmentioning
confidence: 89%
“…Such a feature is commonly observed in fresh preantral follicles of goats (Sharma et al, 1994 andLucci et al, 2001) and other species (cattle: van Wezel andRodgers, 1996 andFair et al, 1997;sheep: Cran et al, 1980 andTassel andKennedy, 1980;guinea pig: Adams and Hertig, 1964;human: Hertig and Adams, 1967;and mouse: Wassarman and Josefowicz, 1978). The association of endoplasmic reticulum with mitochondria and vesicles suggests a mechanism for the transport of substrates into the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the need for an understanding of the ultrastructural events occurring in preantral follicles during preservation in vitro is important to develop suitable preservation systems as well as to comprehend follicular atresia. Furthermore, the ultrastructural features of cattle (Fair et al, 1997), sheep (Tassel and Kennedy, 1980), human Adams, 1967 andOktay et al, 1997), guinea pig (Adams and Hertig, 1964) and goat (Sharma et al, 1994 andLucci et al, 2001) preantral follicles have been described in several papers. In addition, Tassel and Kennedy (1980) and van den Hurk et al (1998) showed the ultrastructural features of preantral follicles that underwent degeneration in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the follicles showed an extreme ooplasm vacuolization, which is a characteristic sign of degeneration and may represent endoplasmic reticulum swelling (Tassel andKennedy, 1980 andSilva et al, 2000), altered mitochondrial structure (Fuku et al, 1995), or cellular necrosis (de Bruin et al, 2002). Therefore, despite being a time-consuming and expensive technique, TEM is an important tool for detecting early morphological changes after follicular culturing in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Although FSH receptors are expressed in granulosa cells (O'Shaughnessy et al, 1996) from the primary follicle stage onward (Oktay et al, 1997), this hormone may act indirectly in the primordial follicles through paracrine factors secreted by larger follicles or stromal cells. Several in vitro studies have demonstrated that FSH promotes the in vitro growth of early caprine preantral follicles and antrum formation in different species after the in vitro culture of large secondary follicles (for a review, see van den Hurk and Zhao, 2005).…”
Section: Introductionmentioning
confidence: 99%